2017
DOI: 10.1093/humrep/dex366
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic control of transposable elements and imprinted genes in newborns is affected by the mode of conception: ART versus spontaneous conception without underlying infertility

Abstract: The study was funded by a grant from Besançon and Dijon University Hospitals. The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…Genetic factors in infertile couples and the variables involved in ART (hormones, culture media, prolonged embryo culture, cryopreservation) may have adverse effects on these epigenetic processes, which are then transmitted to the offspring (Horsthemke and Ludwig 2005;Ceelen et al 2008;Jiang et al 2017). After ART, changes in DNA methylation and/or transcription of some transposable elements and imprinted genes were found in placenta samples while transcription modifications for some transposable elements were also discovered in cord blood (Choux et al 2018). Song and coworkers compared placental DNA methylation levels at 37 CpG sites in 16…”
Section: Epigeneticsmentioning
confidence: 99%
“…Genetic factors in infertile couples and the variables involved in ART (hormones, culture media, prolonged embryo culture, cryopreservation) may have adverse effects on these epigenetic processes, which are then transmitted to the offspring (Horsthemke and Ludwig 2005;Ceelen et al 2008;Jiang et al 2017). After ART, changes in DNA methylation and/or transcription of some transposable elements and imprinted genes were found in placenta samples while transcription modifications for some transposable elements were also discovered in cord blood (Choux et al 2018). Song and coworkers compared placental DNA methylation levels at 37 CpG sites in 16…”
Section: Epigeneticsmentioning
confidence: 99%
“…ART also plays a major role in animal reproduction to increase reproductive efficiency and genetic improvement in livestock, as well as to conserve endangered species. The outcomes of human pregnancies produced by ART have undergone intense scrutiny and while most children conceived using ART are healthy, these procedures have been associated with an increased risk of preeclampsia, intrauterine growth restriction, birth defects (Qin et al, 2016;Zhu et al, 2016b;Choux et al, 2018;Choufani et al, 2019) and imprinting disorders (Market-Velker et al, 2010;White et al, 2015). Although various studies have shown that ART may lead to epigenetic perturbations (El Hajj and Haaf, 2013;Urrego et al, 2014;Duranthon and Chavatte-Palmer, 2018), the etiology associated with ART and increased risk of perinatal complications is still poorly understood.…”
Section: Assisted Reproductive Technology (Art)mentioning
confidence: 99%
“…Although, as highlighted across the literature, the alterations in DNA methylation following ART procedures are not always striking and vary between studies (reviewed in Berntsen et al, 2019), in part because of distinctions in treatments used. It was recently reported that human placenta, but not cord blood, from IVF/ICSI showed decreased DNA methylation levels for imprinted loci H19/IGF2 and KCNQ1OT1, as well as for specific repetitive elements (Choux et al, 2018), whereas in another recent study, no obvious overall differences in genome-wide DNA methylation differences in placental tissues were associated with ART (Choufani et al, 2019). Yet, a subset of ART pregnancies associated with ICSI showed marked decrease in placental DNA methylation levels at imprinted loci (GNAS, SGCE, KCNQ1OT1 and NNAT).…”
Section: Art Proceduresmentioning
confidence: 99%
“…ART techniques, such as controlled ovary hyperstimulation (COH), embryo manipulation, in vitro fertilization, and vitrification are performed during this epigenetic programming period (Ji et al, ). It has been reported that epigenetic disturbances can be found in the cord blood and placentas of neonates conceived via ART (Choux et al, ; Vincent, Gooding, Louie, Chan, & Ma, ). These disorders may impair embryonic and fetal development as well as placental function, thus increasing the risk of pregnancy‐related disease (Bloise, Feuer, & Rinaudo, ; Burton, Fowden, & Thornburg, ; Castillo‐Fernandez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…ART techniques, such as controlled ovary hyperstimulation (COH), embryo manipulation, in vitro fertilization, and vitrification are performed during this epigenetic programming period (Ji et al, 2018). It has been reported that epigenetic disturbances can be found in the cord blood and placentas of neonates conceived via ART (Choux et al, 2018;Vincent, Gooding, Louie, Chan, & Ma, 2016).…”
mentioning
confidence: 99%